Cover Image, Volume 30, Issue 11. Issue 11 (2nd November 2022) - Xu, Sheng; Lin, Xinyu; Zhang, Xiang; Chen, Enguo; Ye, Yun; Guo, Tailiang; Yan, Qun Frank
Abstract : The cover image is based on the Research Article Quantum‐dot color conversion towards white‐balanced healthy displays: Theoretical and simulation study by Sheng Xu et al., https://doi.org/10.1002/jsid.1173